2008
DOI: 10.1037/a0013055
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in family members coping with chronic illness in a relative: An exploratory study.

Abstract: Coping with disability in the family is a multifaceted endeavor entailing changes in all spheres of life. Such changes affect not only the afflicted person but also the immediate relatives. The main objective of this study is to propose a comprehensive definitional framework for the quality of life concept, based on an action systemic approach to meet the challenge suggested in the literature. The work was focused mainly on examining the suitability of the systemic quality of life model for ascertaining life q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This study found that differences in personality and outlook bear a direct impact (either positive or negative) on the quality of life, a finding that is corroborated by other studies (Feigin, Barnetz, & Davidson-Arad, 2008;Langius-Eklöf, Lidma, & Wredling, 2009). However, surprisingly the personality factor did not play a vital role in the issue of disclosure.…”
Section: Downloaded By [University Of Wisconsin-milwaukee] At 19:53 0supporting
confidence: 88%
“…This study found that differences in personality and outlook bear a direct impact (either positive or negative) on the quality of life, a finding that is corroborated by other studies (Feigin, Barnetz, & Davidson-Arad, 2008;Langius-Eklöf, Lidma, & Wredling, 2009). However, surprisingly the personality factor did not play a vital role in the issue of disclosure.…”
Section: Downloaded By [University Of Wisconsin-milwaukee] At 19:53 0supporting
confidence: 88%
“…However, as Giné et al, note, there is no way to ensure that this instruction of responding on behalf of the family has been followed by the family representative [ 58 ]. Feigin et al [ 95 ] understand that the participation of brothers and sisters of the child with disabilities, in addition to the parents, is a requirement of the systemic nature of the family.…”
Section: Discussionmentioning
confidence: 99%
“…QoL of family members related to someone with a chronic illness is lower, specifically, in self-expression, individual growth, and realization of their potentials. 86 Therapy inventions can target those identified areas to resolve emotional and personal conflicts which could prevent emotional burnout. 87 Individualized therapy could focus on other topics unique to the caregiver population, such as the stress between commitment to the sick relative and the needs of the other members in the family.…”
Section: Discussionmentioning
confidence: 99%